Metaphor analysis in the lyrics of Red Hot Chilli Peppers’ “Black Summer” (Passage: Journal of English Language and Literature, 2025)
This research aims to investigate the use of metaphor in the lyrics of the song “Black Summer” by Red Hot Chili Peppers through a stylistic analysis based on Nurgiyantoro’s metaphor classification. The research aims to identify the types of metaphors employed in the lyrics and interpret their contextual meanings within the song’s thematic framework. Using a qualitative descriptive method and a close-reading technique, the study categorizes metaphorical expressions and analyzes them through semantic interpretation and symbolic contextualization. The analysis identifies two types of metaphors: explicit and implicit. The findings show a more substantial presence of explicit metaphors, indicating the lyrical intention to convey emotional states and psychological conditions through direct figurative comparisons. Meanwhile, implicit metaphors appear in subtler symbolic forms, emphasizing indirect emotional nuances. Both types of metaphors contribute to constructing layers of meaning related to emotional alienation, inner conflict, psychological turbulence, and existential uncertainty depicted in the song. Overall, metaphor in “Black Summer” functions not only as an aesthetic feature but also as a conceptual tool to articulate complex emotional experiences and existential struggles. The study highlights the role of figurative language in shaping thematic depth and emotional tone in contemporary English song lyrics. The results are expected to support further stylistic research, particularly those examining metaphor in modern music discourse and exploring how linguistic creativity reflects psychological and cultural expression.